CONTRIBUTIONS OF ACADEMIC MONITORING IN CLINICAL PRACTICES IN ADULT HEALTH FOR THE TRAINING OF THE BEING NURSE: AN EXPERIENCE REPORT - da Silva Fonseca Lima, Gabriely; de Fátima Neves, Luciene; Cristina Rodrigues, Camila (Health and Society, 2023)
Introduction: The academic monitoring program is offered by higher and technical institutions, aiming to provide the student monitor the opportunity to experience the experiences of the teaching and learning process, under the supervision of the teacher, in addition to improving their technical scientific knowledge and skills. Objective To report the importance of the experience lived during the academic monitoring of the subject of Clinical Nursing Practices in Adult Health: minimal and intermediate care, to value and awaken the interest of students in this activity, and to inquire how the monitoring contributes to the formation of nurses. Method: This is a descriptive study, based on the experience report regarding the monitoring of the subject of Clinical Nursing Practices in Adult Health: minimal and intermediate care, developed during the practical activities of the baccalaureate course in Nursing of private University Center in Alto Tietê, from March to June 2022. Description of the monitoring activities: The subject of Clinical Nursing Practices in Adult Health: minimal and intermediate care is part of the mandatory curriculum of the undergraduate course in Nursing, being offered in the 4th and 5th periods, with a workload of 60 (sixty) hours, whose monitoring consisted of helped teacher in the practical activities developed according to the syllabus and class schedule of the discipline. Final Considerations: The monitoring program of this monitoring exceeded the expectations of the student monitor, generating a deepening of her knowledge as well as the essential skills to be a nurse, highlighting communication - which is essential for the establishment of exchange relationships between the student monitor, teacher and students.